The Role of Liquidity Management on The Profitability of Islamic Commercial Banks in Indonesia - Muhammad Ryan Fahlevi; M. Fajar Rizky Heryanto; Aan Shar (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2026)
Purpose:This research is designed to comprehensively examine how liquidity management practices influence the ability of Islamic commercial banks in Indonesia to generate profits, considering that liquidity control represents a major challenge because Islamic financial contracts must adhere strictly to sharia principles and because Islamic banks face restricted access to diverse money market instruments, making the understanding of liquidity profitability interaction essential for long term financial resilience.Design/Methodology:This study applies a descriptive quantitative methodology by relying on secondary datasets obtained from official Islamic banking statistical reports released by the Financial Services Authority (OJK), focusing on Islamic Commercial Banks operating in Indonesia throughout the 2021–2024 timeframe, where liquidity conditions are evaluated through the Financing to Deposit Ratio (FDR) and profitability levels are assessed through Return on Assets (ROA), with analytical emphasis on annual trends, mean values, and changes over time.Findings:The findings of the study reveal a consistent upward movement in both FDR and ROA ratios over the observation period, where the rising FDR signifies a more efficient allocation of third party funds and the growing ROA demonstrates enhanced profit generation, suggesting that sound liquidity management supports profitability performance in Islamic banks despite the absence of a perfectly proportional relationship.Practical Implications:The conclusions of this research offer valuable considerations for banking executives and regulatory authorities when developing liquidity management policies that aim to simultaneously safeguard financial system stability and promote higher profitability within the Islamic banking sector.Originality/Value:This study provides an academic contribution by presenting a detailed descriptive examination of liquidity and profitability patterns in Islamic Commercial Banks, thereby enriching existing literature that has predominantly emphasized quantitative testing of cause and effect relationships.